Advanced Pediatric-Type Follicular Lymphoma, Consequences of a Late Presentation in a Resource-Poor Setting: Case Report and Literature Review - Anthony Chibueze Nlemadim; Theophilus Ipeh Ugbem; Gabriel Unimke Udie; Godwin Cletus Omini; Eghomwanre Davis Izekor; Olufunke Folaranmi Adedokun; Ekaete Joseph Asuquo; Martin Madu Meremikwu; Friday Akwagiobe Odey (Indian Journal of Medical and Paediatric Oncology)
Pediatric-type follicular lymphoma (PFL) is a rare, nonaggressive, slow-growing (indolent), non-Hodgkin lymphoma that is typically seen in males as a localized disease with excellent outcomes. It is largely different from follicular lymphoma (FL). Few published studies on PFL are case series in developed nations. We report on a patient with advanced PFL, a 14-year-old female with 5-year history of neck swellings, abdominal distension for a month, and pericardial effusion, among others. The swellings waxed and waned; and involved all the peripheral lymph nodes. Tuberculosis (TB) GeneXpert and human immunodeficiency virus (HIV) screening were negative. She received anti-TB drugs prior to presentation in our hospital where nodal histopathology showed effaced architecture with diffuse follicles and abundant blastoid cells as well as negative CD5 and BCL2, and positive CD10 and CD20. Diagnosis of PFL (stage 3) was made. She completed six courses of cyclophosphamide, doxorubicin, vincristine, and prednisolone and is well 9 months after therapy. The PFL usually presents with stage 1 or 2 disease unlike in the index female case that was also complicated by effusion and ascites due to late presentation. It responded to chemotherapy and has not reoccurred; in contrast to classic FL and reactive follicular hyperplasia (RFH) which should be differentiated from PFL. Although RFH can be caused by TB or HIV, they are not causes of malignant lymphadenopathy. Physicians should be aware of PFL which may present in high clinical stages, but still retain its good prognosis, for the purposes of counseling.